(untitled) (Global Conference on Medical and Health Sciences, 2026)
This article comprehensively analyzes the role, opportunities, and problems of modern information technologies and media education in the education system. In the context of today’s globalization, the internet, multimedia, and virtual technologies are becoming an integral part of the educational process. The article extensively covers the educational and upbringing potential of mass media, showing their positive and negative impacts. In particular, it is noted that multimedia tools facilitate the process of memorizing information in students, develop independent thinking, and stimulate creative activity. The article also highlights the role of media education within the new paradigm of 21st-century education, the possibilities of using digital educational resources, and the active participation of teachers and students in acquiring new knowledge. The article discusses not only the role of media education in schools and higher educational institutions, but also its influence on the spiritual world of students, their communicative, aesthetic, and intellectual development. In general, the article shows that scientific and methodological approaches are necessary for the effective organization of media education, and the proper management of technologies makes the educational process more effective, interesting, and creative.